Establishing Local Diagnostic Reference Levels and Reference Curves for Thorax and Abdomen-Pelvis Paediatric CT Procedures - Dastikas, Rokas; Jreije, Antonio; Gricienė, Birutė (Acta medica Lituanica, 2025)
Background: Computed tomography is a highly informative diagnostic tool, but its use poses the challenge of managing potentially high radiation exposure to patients. Children are particularly vulnerable to the harmful effects of ionizing radiation, and the growing use of paediatric Computed Tomography (CT) scans has been linked to an elevated lifetime risk of cancer and an increased mortality. The aim of this study was to evaluate local radiation exposure doses in paediatric thoracic and abdominal-pelvic CT exams, to establish Diagnostic Reference Level (DRL) curves, propose local diagnostic reference levels, and compare them with the existing literature and the European Guidelines on Diagnostic Reference Levels for Paediatric Imaging (PiDRL).Materials and Methods: A dataset of thoracic and abdominal-pelvic CT exams performed on children was analysed. Scan data entries were grouped according to the patient weight in the following intervals: 5 to 14 kg, 15 to 29 kg, 30 to 49 kg, and 50 to 79 kg. In each weight group, the minimum, first quartile, median, third quartile, and the maximum values of Volumetric Computed Tomography Dose Index (CTDIvol) and the Dose Length Product (DLP) were calculated. The relationship between CTDIvol, DLP, and the patient body weight was assessed by using exponential curves.Results: The local DRLs were established for thoracic CT exams, while, for abdominal-pelvic CT exams, the DRL curve was set as a substitute due to limited data. The proposed local DRL values for thoracic computed tomography examinations are 2.0, 2.4, 3.6, and 5.0 mGy for CTDIvol and 40, 60, 116, and 156 mGy·cm for DLP in the corresponding weight groups of 5 to 14 kg, 15 to 29 kg, 30 to 49 kg, and 50 to 79 kg. The median values of CTDIvol for paediatric abdominal-pelvic computed tomography were 2.8 mGy in the 5-to-14 kg weight group, 3.6 mGy in the 15-to-29 kg group, 4.8 mGy in the 30-to-49 kg group, and 7.9 in the 50-to-79 kg group. The median DLP values were 81, 127, 203, and 304 mGy·cm, respectively.Conclusions: The set local DRLs for thoracic and the median dose values in abdominal-pelvic CT exams are generally lower than the European DRLs. The derived DRL curves fulfil the same purpose as weight-group DRLs, serving as benchmarks for dose optimization.
Keywords: paediatric; diagnostic reference levels; diagnostic reference level curves; thorax computed tomography; abdomen-pelvis computed tomography